Efficacy of Sorafenib Combined With Immunotherapy Following Transarterial Chemoembolization for Advanced Hepatocellular Carcinoma: A Propensity Score Analysis - Qin, Jian; Huang, Yusheng; Zhou, Hanjing; Yi, Shouhui (Frontiers in Oncology, 2022)
Aim:To compare the efficacy and safety of monotherapy with a sequential immune checkpoint inhibitor (ICI) programmed cell death protein-1 (PD-1) and its combination with multi-target drug sorafenib after transcatheter arterial chemoembolization (TACE) for advanced hepatocellular carcinoma (HCC). Methods: We conducted a retrospective evaluation of patients with advanced HCC who had received sequential PD-1 sorafenib (duplex group, n = 25) or monotherapy PD-1 alone (PD-1 group, n = 41) after TACE during April 2018–September 2021. Propensity score matching (PSM) was applied to correct the selection bias, and 22 pairs were created. The objective response rate (ORR), duration of the overall response (DOR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and adverse events were analyzed for both groups. Results: After PSM, the median PFS (7.63 vs. 2.9 months; p = 0.0335) was significantly longer for the duplex group than for the PD-1 group. The median OS (21.63 vs. 16.43 months; p = 0.103) was longer for the duplex group than for the PD-1 group, albeit without any statistical difference. The CR rate, ORR, DCR, and PFS rates at the first, third, and sixth months were higher for the duplex group than for the PD-1 group, wherein the third and sixth months' PFS rate were statistically different. The OS rates at the sixth, 12th, and 18th months were better for the duplex group than for the PD-1 group, while the 18th-month OS rate (54.5% vs. 33.9%, p = 0.030) were statistically different between them. The most common adverse events after TACE included liver function injury, leukocytopenia, and thrombocytopenia, albeit without any statistical differences between the groups. Cox regression analysis showed that sorafenib combined immunotherapy after TACE and the achieving of CR or PR during the treatment were independent factors affecting PFS. Moreover, CNLC stage-IIIa, TACE frequency ≤2, and achievement of CR or PR were independent influencing factors of OS. Conclusions: Sequential PD-1 combined with sorafenib therapy after TACE for advanced HCC treatment is safe and effective, especially for patients with good initial treatment response, to further improve the disease prognosis.